Language Club as the Medium to Maximize Students’ Speaking Ability - Mutmainah, Rodiatul; Perdana, Purnama Rika; Hillalliyati, Najmi; Muharram, Dimas P. (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2025)
Speaking, as one of four language skills, is vital in people interaction and communication. Since speaking is the foundation of communication, which develops as a result of learning, it is the most crucial part of language learning. This study intends to: 1) describe the implementation of Language Club to maximize students’ speaking skills, and 2) characterize students' responses to certain speaking communities, such as the Learning Club. This study used a descriptive qualitative design. The researcher conducted direct interviews with members and supervisors using a questionnaire to gather data. The questionnaires were given to the Language Club tutors and students. The results show that the Language Club enhances students’ speaking skills supported by the latest media and technology. Besides, positive responses about the language club arise from students. They enjoy the activities and find the club more effective for practicing speaking skills than regular classes. Challenges, such as lack of vocabulary, confidence, and occasional laziness, can be solved by students and they are motivated to overcome these obstacles. Overall, the language club plays an important role in improving students’ speaking skills by providing a dynamic and supportive environment that complements traditional language learning methods.